Understanding Liberals and Conservatives. (March 2014) - Benson, John E.
Abstract It is helpful to teach students of religion and theology that it's not just the teachings and practices of a religion that are important, but the way in which these beliefs and practices are handled that's critical, whether in a liberal or a conservative way. Recent work in Cognitive Linguistics has helped pastors and religion teachers introduce this other dimension of their subject in new ways.